Acute pulmonary artery thromboembolism treated with thrombolysis: diagnostic and monitoring uses of transoesophageal echocardiography. Issue 5 (May 1993) - Rittoo, D; Sutherland, G R
Abstract : The central pulmonary arteries and any thrombus within them can be imaged by transoesophageal echocardiography. Its use is reported in the diagnosis and subsequent management of a patient with acute pulmonary embolism, whose response to thrombolytic treatment was monitored by further transoesophageal studies. Transoesophageal echocardiography may be a valuable primary diagnostic procedure in patients who seem to have sustained a significant pulmonary embolus and require urgent intervention.